Macroscopic and histopathological description of gastric lesions in horse, donkey, and mule fetuses in the last trimester of gestation (2024)
ABSTRACT: Background: Limited information is available on gastric diseases in neonatal foals as compared with extensive studies in young, adult, and geriatric horses. Reports on fetuses are scarce.Objectives: Assess at necropsy stomachs of horse, donkey and mule fetuses in the third trimester of gestation to characterize lesions present during intrauterine life. Animals: Forty-six fetal stomachs from both sexes (21 horses, 21 donkeys, and 4 mules) in the third trimester of gestation were collected from a processing plant immediately after slaughter. Methods: Measurements of longitudinal and transverse axes, weight and volume and gastric fluid pH were taken, and glandular and squamous mucosae were inspected. All findings of the gastric mucosa and measurements of the stomachs were presented descriptively. Groups were compared statistically, with significance level set at P < .05 for all evaluations. Results: All gastric contents had pH >5.8, and mules had larger stomachs and higher weights compared with horses (P < .05). Macroscopic lesions were classified as hyperemic, punctate, and erosive. Histopathologically, lesions were consistent with a chronic inflammatory process. Conclusions and Clinical Importance: Our study provides evidence of macroscopic and histopathological lesions in the gastric mucosae of equid fetuses in the last trimestre of gestation. Relevant information for perinatology and neonatology is provided regarding the prevalence and classification of preulcerous lesions in equids before birth.